2019
DOI: 10.1016/j.bbamem.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological interrogation of asymmetric droplet interface bilayers reveals surface-bound alamethicin induces lipid flip-flop

Abstract: The droplet interface bilayer (DIB) method offers simple control over initial leaflet compositions in model membranes, enabling an experimental path to filling gaps in our knowledge about the interplay between compositional lipid asymmetry, membrane properties, and the behaviors of membrane-active species. Yet, the stability of lipid leaflet asymmetry in DIBs has received very little attention, particularly in the presence of peptides and ion channels that are often studied in DIBs. Herein, we demonstrate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 68 publications
2
52
0
Order By: Relevance
“…A very recent and interesting work by Abbasi et al [28] reported the dampening effect of Alm ion channel on conductivity by an order of magnitude upon introducing an amiloride molecule, which does not inhibit the ion channel formation itself. Taylor et al [29] showed that Alm peptides can induce lipid flip-flop even in a surface-bound state by disordering lipids in the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…A very recent and interesting work by Abbasi et al [28] reported the dampening effect of Alm ion channel on conductivity by an order of magnitude upon introducing an amiloride molecule, which does not inhibit the ion channel formation itself. Taylor et al [29] showed that Alm peptides can induce lipid flip-flop even in a surface-bound state by disordering lipids in the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Here the challenge lies in distinguishing the rate of flip-flop from the rate of lateral lipid diffusion [58] between the monolayer and bilayer, as well as lipid uptake into the bilayer [5,50,59]. However, a recent publication has demonstrated a promising technique for determining bilayer flip-flop on DIB membranes via parallel capacitance-based measurements on an integrated microfluidic device; in this study, it was successfully shown that surface-bound peptides (alamethicin) facilitate the movement of lipids between leaflets [9].…”
Section: Resultsmentioning
confidence: 99%
“…In essence, both dynamical actions are intrinsically linked to bilayers and their compositional stability. Previous studies have externally induced reorganization of lipids by outside factors as seen in model phospholipid membranes upon the addition of cations (4), detergents (5), and peptides (6)(7)(8)(9). Here, we focus on how common organic solvents also impact these dynamics.…”
mentioning
confidence: 99%